Hubungan Antara Komunikasi Interpersonal Kepala Sekolah Dengan Motivasi Kerja Pada Guru Sekolah SMP Islam Namira Medan - Prasetyo, Agung; Syafrizaldi, Syafrizaldi (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2024)
This article or writing aims to look at the relationship between the principal's interpersonal communication and work motivation among teachers at the Namira Islamic Middle School in Medan. The sampling technique used the Total Sampling Technique with a total of 30 people. Using the Likert scale technique, namely the interpersonal communication scale and work motivation scale. This analysis uses the Kolmogorov Smirnov technique with the help of the SPSS version 25.0 for Windows computer program. What is used is that if p 0.05 then it is declared normal and conversely if p 0.05 then the distribution is declared abnormal. This means that the hypothesis proposed by this research is that there is a positive relationship between interpersonal communication and work motivation. That the principal's interpersonal communication is classified as very high. This can be seen from the comparison of the empirical average (74.73) which differs more than the SD amount (15.803) with the hypothetical average value (72.5). Then work motivation is classified as very high. This can be seen from the comparison of the empirical average (70.43) which differs more than the SD number (17.399) with the hypothetical average value (62.5).